'Spoken North Welsh': Henry Sweet's Collaborators in Nant Gwynant. (2nd July 2016) - Awbery, G. M.
Abstract: Henry Sweet's pioneering study of a Welsh dialect, "Spoken North Welsh", appeared in the 1882–84 volume of the Transactions of the Philological Society, and has been an important influence on Welsh dialectologists over the years. Very little attention has been paid, however, to the social context in which he carried out the fieldwork on which it is based. This paper looks more closely at how he interacted with the local community, and uses documentary sources normally associated with research on family history to cast light on the background of the people who helped him to learn Welsh and research the dialect. It appears that the informants who worked with Henry Sweet were respectable and prosperous members of the community, and do not conform to the stereotypical expectations of more recent dialect surveys, which assume that informants should be of the older generation, have little or no education, and have always lived locally. A similar exploration of the context in which other pioneering dialectologists worked may cast new light on the early development of the field.